Redefining Evil: An Interdisciplinary Perspective on Psychological Traits and Societal Perceptions - Čekić, Elvira (International Journal of Psychology, 2025)
Purpose: This study aims to explore the multidimensional aspects of the phenomenon of evil from a psychological perspective, with particular emphasis on the interaction of biological predispositions, evolutionary adaptations, and personality traits that contribute to its manifestation. Methodology: The research adopts a qualitative methodological approach, employing content analysis as the primary technique for synthesizing interdisciplinary data. This method allows for an in-depth examination of the psychological mechanisms underlying moral disengagement and the rationalization of violence, aspects that cannot be fully captured by quantitative methodologies. Case studies are used to identify key cognitive and affective components of malevolent behavior, including dehumanization, empathy deficits, and moral disengagement, while comparative analysis is applied to investigate variations in the perception of evil across different social and cultural contexts. The selection of case studies is based on psychological profiling of violent offenders and authoritarian political figures implicated in mass atrocities, facilitating a comparative exploration of individual and collective mechanisms of moral disengagement. Additionally, the study employs a hermeneutic interpretative framework to examine the dynamic interplay between intrapsychic, cognitive, and societal factors that contribute to the normalization of destructive conduct. Findings: The study identifies empathy deficits as a central etiological factor in the development of aggressive and antisocial behavioral patterns, emphasizing the role of moral dilemmas in cognitive-affective processing underlying ethical decision-making. Dehumanization emerges as a core psychosocial construct that facilitates the cognitive restructuring of moral transgressions, thereby reducing both individual and collective moral accountability. Moreover, findings indicate that sensationalized media representations of violence perpetuate negative cognitive schemas and reinforce social prejudices, ultimately contributing to the stigmatization of victims and the normalization of aggression. These insights underscore the necessity of implementing evidence-based educational interventions aimed at enhancing moral reasoning, fostering empathy, and building resilience against socio-cognitive distortions that legitimize violence. Such interventions hold particular significance in the context of forensic rehabilitation programs and preventive strategies in educational settings, helping to counteract the internalization of maladaptive cognitive frameworks that sustain destructive behavioral tendencies. Unique Contribution to Theory, Practice, and Policy: The theoretical contribution of this study lies in its emphasis on the neuropsychological underpinnings of empathy, particularly focusing on the neurocognitive substrates of moral judgment and affective regulation. Psychologists and neuroscientists can leverage these insights to refine clinical models of moral cognition and emotional regulation in individuals with aggressive tendencies. Educators and policymakers can integrate these findings into psychoeducational programs aimed at fostering moral sensitivity, enhancing prosocial behavior, and reducing implicit biases in children and adolescents. Legal professionals and forensic psychologists can apply this knowledge in the development of therapeutic jurisprudence frameworks and rehabilitation strategies that target cognitive-affective mechanisms implicated in antisocial conduct. At the policy level, the study advocates for the implementation of legal and institutional measures that promote victim destigmatization and ethical standards in media representations of violence, thus counteracting narratives that legitimize aggression and reinforce systemic moral exclusion.